Simulasi Sistem Pengendalian Motor Stepper dengan Metode Pulse Width Modulation - Timothy Wijaya, Hans; Pangestu, Devin; Timothy Sutjipto, Marcellus; Surya Widjaja, Williem; Octavianus Bachri, Karel; Nur, Tajuddin (Jurnal Elektro, 2022)
This paper discusses the control of a stepper motor using Pulse Width Modulation (PWM) methods. In this paper, the author presents two designs: one using a stepper motor controller with an astable multivibrator as a pulse generator and the other utilizing a microcontroller as the pulse generator. The design of the stepper motor controller with an astable multivibrator involves using the IC timer 555 to control the stepper motor speed and a latch circuit to control the direction of the stepper motor rotation. Meanwhile, the design of the stepper motor controller with a microcontroller employs the Arduino UNO R3 to control both the direction and speed of the stepper motor. Testing is conducted through a simulation of the system design using Proteus software. From the test results, it is observed that an increase in the PWM value leads to a faster rotation speed of the stepper motor, conversely, a decrease in PWM value results in a slower rotation speed of the stepper motor.